The distribution of thiamin and pyridoxine in the western tropical North Atlantic Amazon River plume - Barada, Laila P.; Cutter, Lynda; Montoya, Joseph P.; Webb, Eric A.; Capone, Douglas G.; Sanudo-Wilhelmy, Sergio (Frontiers in Microbiology, 2013)
B-vitamins are recognized as essential organic growth factors for many organisms, although little is known about their abundance and distribution in marine ecosystems. Despite their metabolic functions regulating important enzymatic reactions, the methodology to directly measure different B-vitamins in aquatic environments has only recently been developed. Here, we present the first direct measurements of two B-vitamins, thiamin (B1) and pyridoxine (B6), in the Amazon River plume-influenced Western Tropical North Atlantic (WTNA) Ocean, an area known to have high productivity, carbon (C) and dinitrogen (N2) fixation, and C sequestration. The vitamins B1 and B6 ranged in concentrations from undetectable to 230 pM and 40 pM, respectively. Significantly higher concentrations were measured in the surface plume water at some stations and variation with salinity was observed, suggesting a possible riverine influence on those B-vitamins. The influences of vitamins B1 and B6 on biogeochemical processes such as C and N2 fixation were investigated using a linear-regression model that indicated that the availability of those organic factors could affect these rates in the WTNA. In fact, significant increases in C fixation and N2 fixation were observed with increasing vitamin B1 concentrations at some low and mesohaline stations (stations 9.1 and 1; p value <0.017 and <0.03, respectively). N2 fixation was also found to have a significant positive correlation with B1 concentrations at station 1 (p value = 0.029), as well as vitamin B6 at station 9.1 (p value <0.017). This work suggests that there can be a dynamic interplay between essential biogeochemical rates (C and N2 fixation) and B-vitamins, drawing attention to potential roles of B-vitamins in ecosystem dynamics, community structure, and global biogeochemistry.